Processus acquisitionnels des langues par les médias. L’apport des nouvelles technologies en compréhension orale chez les apprenants de 4eme année moyenne Difficultés, enjeux et perspectives - Mohammed Zeher (My University, 2012)
The teaching of French language in Algeria is above all to provide the learner with the same language skills enable them to impart information to receive it is also a way of opening to the world, science and new techniques. The learner must be in harmony with the many advances that surrounds point or it can integrate and become a successful player and influential His other goal too even more important than ever is to access the documentation the multimedia solution could be a transmission belt incentive a strong motivating and exciting way and possibly could help the advocates of self-learning and acquisition of skills and language skills consistent.